THE IMPACT OF DIGITAL TRANSFORMATION ON THE PREPARATION OF GOVERNMENT BUDGETS: NEW APPLICATIONS AND USES OF ARTIFICIAL INTELLIGENCE IN E-GOVERNMENTS - Sumaya Mahdi Thwaini (Scholar Express Journals, 2025)
The public financial management digital transformation has introduced paradigm shifts in the way governments approach preparing and executing public budgets. This study examines the digital transformation impact, the integration of artificial intelligence (AI), on public budgeting processes within e-government. It shows how emerging digital technologies help automating budgeting tasks, improve the financial forecast accuracy, and enhance both transparency and efficiency in fiscal decision-making. By a mixed-method approach joining literature review and empirical analysis, data was collected from employees in public financial departments. The results show a growing awareness of digital tools and a positive perception of AI’s role in the improvement of budgetary performance, despite the concerns about implementing challenges and data security. The study introduces practical recommendations for policymakers to enhance the digital adoption in budgeting and stresses the need for capacity-building programs for supporting a sustainable digital transition in the public sector
Keywords: Digital Transformation; Public Budgeting; Artificial Intelligence